Research on polymer solution rheology in polymer flooding for Qikou reservoirs in a Bohai Bay oilfield - Leilei Tie; Meng Yu; Xiang Li; Wenhui Liu; Bo Zhang; Zhen Chang; Yufei Zheng (Journal of Petroleum Exploration and Production Technology, 2018)
Abstract This study explored the potential applications of three newly modified polymers [a linear polymer, a hydrophobic association of partially hydrolyzed polyacrylamide (HAHPAM), and a polymer–surfactant] as flooding agents in a specific oilfield. Rheological measurements were performed to examine the rheological performances of the three polymers under reservoir conditions. Their stability, viscoelasticity, and propagation properties were analyzed under simulated reservoir conditions. Propagation performance analyses were conducted in a sandpack model to study the propagation behavior of the three polymers in porous media. The results of the rheological study showed that the HAHPAM and polymer–surfactant exhibited high viscosity at low shear rates (deep reservoir), and all three showed acceptable viscosity with good injectivity at high shear rates (near wellbore area). In oscillatory deformation tests, the HAHPAM and polymer–surfactant showed a predominantly elastic behavior. The results of the propagation performance showed the linear polymer and polymer–surfactant could propagate well in porous media, whereas the HAHPAM showed poor propagation behavior. This finding contrasted with rheological tests in which the injectivity of HAHPAM was superior, with high viscosity at low shear rates. The results of the study provided insights either into matching the viscoelastic performance with propagation behavior in porous media, or upon analyzing the suitability of the polymers for flooding throughout a whole process under “from injectivity to propagation” considerations.